Meningkatkan Kompetensi Digital melalui Integrasi Teknologi dalam Pendidikan Kejuruan - Hermansah, Bambang; Setywati, Heny; Nasuka, Nasuka; Setiawaty, Elika (Pandawan Sejahtera Indonesia, 2025)
The rising demand for digitally skilled workers in the 21st century has necessitated a transformation in vocational education through the integration of technology to enhance students digital competencies. This study investigates how incorporating digital technologies into vocational learning environments can improve students digital skills and readiness for the modern workforce. Focusing on vocational schools in urban areas, the study targets students from technical and business-related programs. Employing a mixed-methods approach, data were collected through quantitative surveys and qualitative interviews involving both students and teachers. The results show that while digital tools like learning management systems, simulations, and online collaboration platforms are generally available, their effective pedagogical use is inconsistent across institutions. Students who learned in structured digital environments exhibited higher levels of digital literacy, adaptability, and problem-solving capabilities using technology. Additionally, the study highlights the pivotal role of digitally competent teachers in ensuring successful technology integration and enhancing student learning outcomes. The research concludes that technology integration not only strengthens digital competencies but also promotes active learning aligned with industry needs. To address the digital skills gap effectively, vocational institutions must prioritize both infrastructure development and ongoing professional development for educators. These efforts are essential to foster sustainable, relevant, and future-oriented vocational education in the digital age.